The grey fovea sign of macular oedema or subfoveal fluid on non‐stereoscopic fundus photographs. Issue 1 (2nd August 2016) - Hasler, Pascal W.; Soliman, Wael; Sander, Birgit; Haamann, Per; Larsen, Michael
Abstract: Purpose: To describe the grey fovea sign of fovea‐involving macular oedema or subretinal fluid accumulation in red‐free fundus photography. Methods: A test set of 91 digital fundus photographs of good quality from 100 consecutive eyes in 72 patients with diabetic retinopathy or central serous chorioretinopathy was composed by one of the investigators and evaluated by four masked observers. The photographs were graded as to whether a normal dark fovea was present or absent. The reference method was foveal thickness measurement using optical coherence tomography (OCT). Results: Eyes graded as having a grey fovea on fundus photographs ( n = 67) had a median foveal thickness of 279 μ m (interquartile range 130 μ m), whereas eyes graded as having a normal dark fovea ( n = 24) had a median foveal thickness of 238 μ m (interquartile range 44.5 μ m, p = 0.025). Conclusion: The absence of a dark fovea on red‐free greyscale fundus photographs is a sign of foveal thickening or detachment that can be reliably recognized by graders when using OCT as the reference diagnostic method. Awareness of the grey fovea sign may facilitate fundus photographic screening for maculopathy because its absence is a reliable sign that no foveal oedema or detachment is present. Its presence may indicate that such conditions are present, but it can also be induced by various other conditions, for which reason it should prompt further investigations by OCT.